Counseling on Good and Healthy Eating for “Jelita” Women (Approaching 50 Years) - Irma Muhsen; Ayu Sri Wahyuni; Andi Kamal M Sallo; Safriadi Darmansyah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Ahead of the holy month of Ramadan, culinary tourism in the city of Makassar is enlivened with various festivals. The government also supports the implementation of food festivals through the "Makassar City, Good Eating City" program. Various specialties of Daeng City will be a treat for the community, including "beautiful" women (approaching 50 years). Age is not easy anymore, and the physiology of the body, which has changed a lot, makes them have to pay attention to diet. Counseling on good and healthy eating aims to socialize good ways of eating with the right portions. This counseling was attended by 25 elderly women who live in the city of Makassar. It is recommended to consume foods with complete macronutrients in the form of carbohydrates, proteins, and fats in the correct portion. Thus, all the nutrients that the body needs are fulfilled, so that the body remains fit during fasting.